PEMAKAIAN GAYA BAHASA SINDIRAN SEBAGAI BENTUK KRITIK SOSIAL DALAM ACARA “MATA NAJWA” DI TRANS7 (THE USE OF SATIRE LANGUAGE STYLE AS A FORM OF SOCIAL CRITICISM IN MATA NAJWA TALKSHOW ON TRANS7) - Frisca Dilla; Syahrul Ramadhan (Balai Bahasa Jawa Barat, 2021)
The use of a distinctive language style aims to show the richness of language in conveying intent and purpose. One of the interesting national television programs discussed in terms of language style usage is Mata Najwa on Trans 7. This study aims to explain the form of the use of Najwa Shihab's satire language style and its meaning as a form of social criticism towards government on Mata Najwa. This research method is a qualitative descriptive study using a pragmatic stylistic approach. The results showed that the cynicism language style was the most widely used language style on Mata Najwa. The use of language style between the speaker and the presenter prefers to use language that tends to be a bit harsh and seems to hurt the other person with ridicule or direct speech. In contrast to the irony and inuendo's language style, very few appeared in the event.